O myśleniu i działaniu po polsku - Przesmycki, Piotr (Annales. Etyka w Życiu Gospodarczym, 2010)
This article entitled „On the Thinking and Feeling in Polish” is an essay, a literary– scientific form of presenting the author`s view on Polish mentality. The author analyzed first the sphere of thought, and then he passed to the voluntarily – emotional sphere and finally he describes the patriotism of the Poles. His opinions are based on the characteristics of deep-rooted in the „Polish soul”, and repeatedly expressed in many ways in the area of Polish history and culture. Both in structure and in this matter, the author refers to the presentation of the „essential content of Polish thinking and feeling” by Fr. prof. Stanislaus Olejnik – nestor of the polish moral theologians. This article „On the Thinking and Feeling in Polish” is both a voice in the still ongoing discussion about „the Poles own portrait”.